2012
DOI: 10.1016/j.coal.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Basin evolution and coal geology of the Donets Basin (Ukraine, Russia): An overview

Abstract: Мета. Метою роботи є розроблення концепції геодинамічного розвитку зсувної дислокаційної зони Західного Донбасу (ЗД) на основі аналізу результатів визначення природної газоносності на прикладі ділянки розвідки Свидівська з використанням сучасних засобів опрацювання інформації та візуалізації; встановлення головних закономірностей впливу зсувної тектоніки на формування газових скупчень у вугленосних відкладах ЗД. Методика. Для аналізу структурно-геологічної інформації застосовані методи цифрової геологічної кар… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 23 publications
1
46
0
2
Order By: Relevance
“…1). The basin represents a deep intra-cratonic rift with up to 22 km of sediments spanning the mid-Devonian-Cenozoic and is characterised by a WNW-ESE trending axis (Lungershausen 1942;Stovba et al 2003;Sachsenhofer et al 2012). The sedimentary successions within the basin are poorly exposed, and knowledge about the sedimentary evolution is derived mainly from sub-surface data.…”
Section: Geological Settingmentioning
confidence: 99%
“…1). The basin represents a deep intra-cratonic rift with up to 22 km of sediments spanning the mid-Devonian-Cenozoic and is characterised by a WNW-ESE trending axis (Lungershausen 1942;Stovba et al 2003;Sachsenhofer et al 2012). The sedimentary successions within the basin are poorly exposed, and knowledge about the sedimentary evolution is derived mainly from sub-surface data.…”
Section: Geological Settingmentioning
confidence: 99%
“…Rudov Beds) together with Serpukhovian to Moscovian coaly layers are potential source rock horizons. Oil window maturity (~0.65 % Rr; random vitrinite reflectance in oil) in the north-western part of the basin is reached at around 3,500 m depth, but at shallower depth in the inverted SE part of the DDB [5,15,16]. Hydrocarbon generation occurred predominantly during Permian deep burial, according to previous basin modelling studies [16].…”
Section: Geological Settingmentioning
confidence: 91%
“…Many scholars have found that coal and gas outbursts are related to geologic tectonism during their investigation of sites where outbursts occurred (Airey, 1968;Cheng et al, 2013;Sachsenhofer et al, 2012;Zhang et al, 2016). Not all tectonic coal will result in coal and gas outbursts; however, tectonic coal was often found in these sites.…”
Section: Introductionmentioning
confidence: 94%